Rekonstruksi Filsafat Sains Islam dalam Mengatasi Dualisme Epistemologi dan Implikasinya terhadap Pendidikan Anak Usia Dini: Studi Konseptual - Suminah; Syamsul Rijal (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2026)
Abstract The philosophy of science from an Islamic perspective is a critical inquiry into knowledge that situates science within the framework of tawhid by integrating revelation, reason, and empirical experience. Unlike the Western scientific paradigm, which tends to be secular and value-neutral, Islamic philosophy of science views knowledge as ethically grounded and oriented toward devotion to Allah and human well-being. This paper aims to examine the concept of Islamic philosophy of science, its ontological, epistemological, and axiological foundations, its differences from the Western paradigm, and its relevance to modern science, particularly in early childhood education. This study employs a library research method through the analysis of relevant scholarly literature. The findings indicate that Islamic philosophy of science offers an integrative, humanistic, and transcendental paradigm capable of addressing ethical and spiritual crises in modern science. In early childhood education, this philosophy provides a foundation for holistic education that balances cognitive development with moral and spiritual formation, contributing to the development of insān kāmil. Keywords: Islamic Philosophy of Science, Tawhid, Modern Science, Early Childhood Education.